Biomarkers of Exposure to Chemical Contamination in the Commercial Fish Species Lepidopus caudatus (Euphrasen, 1788): A Particular Focus on Plastic Additives - Salvaggio, Antonio; Tiralongo, Francesco; Krasakopoulou, Evangelia; Marmara, Dimitra; Giovos, Ioannis; Crupi, Rosalia; Messina, Giuseppina; Lombardo, Bianca Maria; Marzullo, Alessandra; Pecoraro, Roberta; Scalisi, Elena Maria; Copat, Chiara; et al. (Frontiers in Physiology, 2019)
In recent years, the Mediterranean Sea has become an accumulation zone for waste generated by the 22 countries bordering its shores. Although the effects of plastic litter on the marine environment and on organisms have recently been studied in other areas, further information is needed for the Mediterranean Sea and, in particular, about plastics additives inputs and interactions with the biota and the trophic network, such as phthalates and bisphenol A. Plastic material production, use and disposal contribute also to the release of heavy metals into the environment, such as mercury (Hg), often used during the production of chlorine, the primary ingredient in PVC, lead (Pb) and cadmium (Cd), which are used as stabilizers in PVC and leach out of products during use and disposal. Our research aims to evaluate phthalates, bisphenol A and heavy metals contamination in Lepidopus caudatus (Pisces, Trichiuridae), which could be considered as a potential sentinel species. For the evaluation of toxicological effects, we evaluated the expression of vitellogenin and metallotoneins 1. In all samples analyzed, we have not found microplastics in the gastrointestinal tract but chemical analysis revealed the presence of high content of phthalates, and in particular high quantities of DIDP, DEHP, bis-benzylester phthalate, bis-butyl ester phthalate and mono-N-butyl ester phthalate in different organs. Instead, trace elements detected in tissue revealed a trend of concentrations generally higher in liver and intestine than gill and muscle tissues. Immunohistochemical analysis for anti-metallothionein 1 antibody showed a strong positivity of liver cells, both in females and males. Analysis for the anti-vitellogenin antibody showed in females a strong positivity both in the liver cells and in the gonads, in male specimens was found to be always negative except for a specimen, in which it was highlighted a positivity in some areas of the liver and of the gonad.